2018
DOI: 10.26701/ems.471131
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect on Tribological Properties of the use of Pinus Brutia Cone as a Binder in Brake Pads

Abstract: Phenolic resin is invariably used as binder material for friction composites. Alternative materials are considered alternatively to phenolic resin due to negativities such as poor shelf life, harmful volatiles during processing, the need for addition of curing agent before shipment, shrinkage and voids in final products. For these reasons, pinus brutia cones are ground and pulverized and added to the brake lining content at different rates and thus 3 different samples were produced. The wear and friction tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The results showed that different types of fillers had specific functions as friction materials and were combined with the phenolic resin in a fundamentally physical way. Sugözü and Kahya [17], in their studies, used test samples produced with phenolic resin additive at different ratios and added Pinus brutia cone material to the composite as a binder. They compared the phenolic resin and Pinus brutia cone material and obtained the highest coefficient of friction (0.31 µ ) in the KI-8 sample, which contained 8% Pinus brutia cone and 12% phenolic resin.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that different types of fillers had specific functions as friction materials and were combined with the phenolic resin in a fundamentally physical way. Sugözü and Kahya [17], in their studies, used test samples produced with phenolic resin additive at different ratios and added Pinus brutia cone material to the composite as a binder. They compared the phenolic resin and Pinus brutia cone material and obtained the highest coefficient of friction (0.31 µ ) in the KI-8 sample, which contained 8% Pinus brutia cone and 12% phenolic resin.…”
Section: Introductionmentioning
confidence: 99%
“…Today, most of the researchers have focused on the use of industrial and agricultural waste in vehicle brake linings (Sugözü and Kahya, 2018;Ibhadode and Dagwa, 2008;Idris and Aigbodion, 2015). Alternative studies have been made such as hazelnut shell, coconut shell, palm kernel shell for asbestos-free brake linings (Yawas et al, 2016;Akıncıoğlu et al, 2018;Ghazali et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the studies [5][6][7][8][9][10][11][12][13][14][15][16][17], the usability of materials such as aramid fiber, carbon fiber, metal fibers, palm kernel fibers, glass fiber, fly ash fiber, sisal fiber, stone wool fiber and organic fiber as a reinforcement material was investigated experimentally. Necessary tests have been carried out using various materials such as waste vehicle dust, alumina, fly ash, banana peel, powdered pine cone and steel wool as the friction regulator [18][19][20][21][22][23]. In addition, studies on the use of boron products in friction composites [24][25][26][27][28][29] are relatively limited.…”
Section: Introductionmentioning
confidence: 99%